Perception Of The Spiritual Symbol In Armenian Medieval Philosophy And Theology - Alvrtsyan, Haykazun (Տիգրան Մեծ)
The article presents the perceptions and viewpoints of the Armenian medieval literary men concerning the spiritual symbol. Being anchored in the pan-Christian perception of the symbol, it laid the basis of the symbolic-allegorical thinking of the Armenian spiritual culture. In the history of the Armenian medieval literature and art studies, the analysis of symbols, in essence, the discovery of the epiphany in them, which is the fundamental meaning of the culture, have often been neglected. Today there is a necessity to analyse the spiritual culture in a new way to dig out its ideological – world outlook basis conditioned by the artistic and the festival and ritual functions of the different types of art. Such a research also enables us to comprehend the aesthetic, artistic and doctrinal - philosophical merits of the spiritual culture (literature, miniature, architecture, etc.) created throughout the centuries and still unknown to us in a new way, to review the system of criteria and ideological-methodological basis of the evaluation, which bears a great significance for the complete and precise perception and evaluation of the Armenian art and literature of the Middle Ages (see Alvrtsyan, 2017).
Keywords: Theology